Denudation history of the Great Escarpment in the southwestern flank of the Angola (Bié) Dome, Africa - Silva, Bruno V. [UNESP]; Souza, Daniel H.; Hiruma, Silvio T.; Siqueira-Ribeiro, Marli C. [UNESP]; Luvizotto, George L. [UNESP]; Glasmacher, Ulrich A.; Hackspacher, Peter C. [UNESP] (Springer Nature, 2023)
The origin of the topography and relief of southern Africa has been the subject of intense debate. The landscape is characterized by a high, low-relief inland plateau, separated from the low-lying coastal region by a remarkably steep escarpment, known as the “Great Escarpment”. In this paper, we bring new insights into the denudation history of the southwestern Angolan margin by providing new apatite (U-Th-Sm)/He data from the Chela Escarpment, one of the steepest stretches of the African Great Escarpment. In addition, we performed morphometric analysis of the river network to access the interplay between rock uplift and erosion of both the interior and coastal river catchments. The new apatite (U-Th-Sm)/He data combined with previous published thermochronological data show that seaward of the Chela Escarpment summit, the last denudation event commenced at ~ 40–20 Ma, whereas the top of the scarp appears to have undergone the last denudation event at ~ 120–70 Ma with relatively low Cenozoic denudation. The new morphometric data suggest that fluvial incision rates are typically higher for the coastal rivers in comparison to those farther inland, and that as the coastal rivers erode backwards they tend to dissect the plateau surface, causing river captures, and the migration of the drainage divide farther inland. As this margin segment lies at the southwestern side of the Angola Dome, we propose that the Chela Escarpment has been formed primarily by the dissection of the dome flank, since the Late Cenozoic, in a manner comparable to that which (Burke and Gunnell, The african erosion surface: a continental-scale synthesis of geomorphology, tectonics, and environmental change over the past 180 million years, memoir 201, Geological Society of America, Boulder, Colorado, 2008) propose for the Great Escarpment formation in southern Africa. In this scenario, the river network responding to the crustal uplifts and steepening of the land surface, base-level falls, and relatively humid climatic conditions, appears to account for this model of landscape evolution.
Keywords: (U-Th-Sm)/He thermochronology; Angolan margin; Cenozoic uplift; Chela Escarpment; Drainage morphometry; Thermal history modeling